Análisis constitucional de las políticas públicas en los estados de excepción y la seguridad interna - Gómez Cuadro, Ronny Salustio (2025)
In the year 2023, 11 states of exception have been generated, currently in the year 2024; on August 30, 2024, President Daniel Noboa extends a state of exception dictated on July 6, 2024. After this date, without having remedied the reasons that caused the previous states of exception, the President of the Republic, through Executive Decree No. 410, decreed this Thursday, October 3, a new state of exception that will govern for 60 days in cantons of eight provinces of the country, including Quito, the capital and Guayaquil, the second most important city of the nation. In addition, the president declared a curfew in 20 localities. The measures come in the midst of an increase in crime and the intensity of the prolonged presence of illegal armed groups linked to drug trafficking. During 2022 and 2023, Ecuador was immersed in multiple crises that required the application of several states of exception. These crises were mainly characterized by a significant increase in drug-related violence, social unrest and internal security problems. At last, we have managed to generate an analysis of public policies and governance within a state of exception in Ecuador, in order to initiate a more holistic study of this topic.